P.O.W.E.R learning - Feldman, Robert S. (McGraw Hill, 2009)
The only first-year experience text with a unifying system for critical thinking and problem solving, P.O.W.E.R. Learning maximizes students' potential for success in college and in life. Using the simple, class-tested principles of the P.O.W.E.R (Prepare, Organize, Work, Evaluate, and Rethink) system, students gain a sense of mastery and achievement as they move through the text; with the growth of their confidence comes the increased intellectual enthusiasm and personal discipline needed for them to excel